A Study On Insurance Awareness And Its Relationship With Preference And Purchase Decision Among Policyholders In Chennai . - S.Thomas; Dr. A. Elankumaran (Revista Electronica de Veterinaria)
In the rapidly growing insurance sector, enhancing policyholders’ awareness and influencing their purchase decision has become a major concern for insurance providers. Awareness of insurance products plays a crucial role in shaping consumers’ preferences, which ultimately determine their purchase decisions. This study examines the relationship between awareness towards insurance products, preference towards insurance products, and purchase decision among policyholders in Chennai. The study considers awareness of life insurance and health insurance as independent variables, preference based on premium affordability and risk coverage as mediating variables, and purchase intention and renewal decision as outcome variables. Primary data were collected from policyholders using a structured questionnaire. Descriptive statistics, Pearson correlation, and regression analyses were employed to examine the proposed relationships. The results reveal that insurance awareness significantly influences preference, which in turn has a positive impact on purchase decision. The study highlights the importance of improving insurance awareness to strengthen customer preference and purchase behavior.